Thermal Evaporation of Graphene on Silicon: A Molecular Dynamics Simulation - pamungkas, mauludi ariesto; A. B. Gien; F. S. Farista; D. J. D. H. Santjojo (BRIN Publishing (Penerbit BRIN), 2025)
Silicon, a ubiquitous element in modern electronics, underpins the operation of countless devices due to its unique semiconducting properties. However, as device dimensions shrink to the nanoscale, silicon-based devices face limitations such as increased power consumption and decreased performance. Coating silicon with graphene is aimed to improve the device performance and extend the limits of silicon’s performance. Conducting experimental work involving graphene for thin coatings is a resource-intensive process. Hence, molecular dynamics (MD) simulation is necessary to illuminate the evaporation and coating mechanisms at the atomic scale, serving as a valuable tool for experimental design. These molecular dynamics simulations have elucidated the intricate relationship between temperature and deposition time in governing the quantity and spatial distribution of carbon atoms on a silicon substrate. Within a 300 ps deposition interval, a non-linear correlation between temperature and carbon deposition is observed, indicating that the allotted time is insufficient for complete atomic diffusion and homogeneous distribution. At elevated temperatures, carbon atoms accumulate, impeding the diffusion of subsequent atoms. Conversely, a 600 ps deposition period reveals a direct proportionality between temperature and carbon deposition, attributed to the enhanced mobility of carbon atoms, facilitating their dispersion and creation of vacancies within the substrate.